The independence running events in Poland in 2018 - motives of participation. The case study of 8th Edition of the independence run in Luboń - Ewa Malchrowicz-Mośko; Maciej Młodzik; Karolina Chlebosz (Kazimierz Wielki University, 2018)
The purpose of the study was to examine the motivations to participate in a not high class running event and evaluate the socio-demographic profile of a participant. The sample comprised 100 runners that participated in the 8th edition of the Independence Run in Luboń, which took place on November 11, 2018, on the hundredth anniversary of Poland regaining its independence. To evaluate the motivation to participate in the event, a self-constructed questionnaire was used. The results might be useful for sport managers to analyze consumer behavior and utilize the results in their everyday practice, especially in the strategic planning, marketing and implementation of massive sport events which take place outside the limits of a big city.